The Role of MMOGs in English Language Development of EFLStudents - Arini, Rahma Muthia; Pitaloka, Nova Lingga (Universitas Pahlawan Tuanku Tambusai, 2025)
Massively Multiplayer Online Games (MMOGs) are increasingly popular and widely played, but their use as an English language learning medium remains under-recognized. This study aims to analyze the role of MMOGs in developing the English language skills of students in the English Language Education Study Program at Sriwijaya University. This study used a qualitative approach with a case study design and involved five participants who actively used English while playing. Data were collected through semi-structured interviews and game recording documentation, then analyzed using thematic analysis. The results showed that MMOGs were highly effective, increasing students' motivation and complementing formal English learning, as well as supporting the development of speaking, listening, reading, writing, vocabulary, grammar, and pronunciation. Students used English through text chat, voice chat, quests, instructions, and story-lines, so that interactions were natural and meaningful. Thus, MMOGs can be pedagogically utilized as an effective complementary English learning medium by providing educators with alternative strategies to promote authentic and motivating language practice beyond the classroom.